2000
DOI: 10.1590/s1516-31802000000400005
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant efficacy of sertraline and imipramine for the treatment of major depression in elderly outpatients

Abstract: a b s t r a c tCONTEXT: Most double-blind studies of efficacy and tolerability of sertraline as compared to tricyclics in the treatment of late-life major depression have used amitriptyline as a standard, leading to the inevitable conclusion that the former drug is better tolerated than the latter, with both being equally efficacious. OBJECTIVE:To compare the antidepressant efficacy and tolerability of sertraline (50 mg/day) and imipramine (150 mg/day) in the first 6 weeks of the treatment of major depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
7
0
8
Order By: Relevance
“…A expectativa de vida da população mundial, que hoje é de 66 anos, passará a ser de 73 anos em 2025 (1) . No Brasil, é estimado que haverá cerca de 34 milhões de idosos em 2025, o que o tornará o sexto país do mundo em contingente de idosos (2)(3) .…”
Section: O Processo De Viver E De Ser Cuidado De Idosos E a Percepçãounclassified
“…A expectativa de vida da população mundial, que hoje é de 66 anos, passará a ser de 73 anos em 2025 (1) . No Brasil, é estimado que haverá cerca de 34 milhões de idosos em 2025, o que o tornará o sexto país do mundo em contingente de idosos (2)(3) .…”
Section: O Processo De Viver E De Ser Cuidado De Idosos E a Percepçãounclassified
“…Sendo a necessidade de fármacos que atuassem de forma mais rápida e confiavelmente com menos efeitos colaterais que levou a introdução de fármacos inibidores seletivos da captação de serotonina (FORLENZA et al, 2000;RANG et al, 2004). …”
Section: Mecanismo De Ação Dos Antidepressivosunclassified
“…It is noteworthy that negligence refers to the refusal, omission or failure held by the responsible for the elderly and that can result in physical impairment, emotional and social. 6 Studies aimed at investigating the domestic violence against the elderly are scarce in Brazilian scientific literature, although the deepening of knowledge in this area is essential for the formulation of strategies for health promotion, early diagnosis and monitoring of cases of victims and their families. 7 In the health area, a research conducted in Recife-Pernambuco found high prevalence of visits to the elderly, victims of accidents and violence, but noted that this service was still inadequate, presenting deficient regarding the lack of specific clinical protocols for these cases, support the elderly, caregivers and victimizers inefficient, low involvement of endocrine and insufficient training of professionals.…”
mentioning
confidence: 99%